Economic Adversity and Disgrace in Untouchable - Regmi, Bhim Nath (NUTA Journal, 2018)
Mulk Raj Anand has created a unique position as a Humanist and a social writer in India writing in English. He has contributed in the development of Indian English Literature and focuses on caste issue, economic adversity and disgrace rooted in Indian society. He has public concerns and humanity for the subjugated people and his characters represent the social reality of suppressed people of India. His first novel Untouchable is an account of a day in the life of its protagonist- Bakha, an untouchable sweeper. He describes the depressed conditions of the untouchables, their immitigable hardships and physical and mental agonies almost with the meticulous skill of historical raconteur